1995
DOI: 10.1063/1.113759
|View full text |Cite
|
Sign up to set email alerts
|

Fluxon interaction in an overdamped Josephson transmission line

Abstract: We have simulated fluxon propagation within a Josephson transmission line that is one of the elements of a rapid single flux quantum (RSFQ) circuit. This line is a parallel connection of damped Josephson junctions coupled by superconducting inductances. Geometries with and without mutual inductances between neighboring cells are considered. If the time interval between two fluxons is less than 0.3 φ0Vc−1 (Vc characteristic voltage) a repulsion between them was observed. The repulsion sets a specific time delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…For the pulse trains at the frequency of 66.7 and 80 GHz, the jitter saturates with increasing number of junctions. Kaplunenko suggested that SFQ pulses propagating through a JTL repulse each other when the time interval between adjacent pulses is smaller than that corresponding to the specific frequency, [8]. The value of specific frequency estimated for the parameters of junctions fabricated by NEC's Nb standard process is about 50 GHz, which agrees with the result of simulation.…”
Section: B Sfq Pulse Behaviors In Jtlsupporting
confidence: 81%
“…For the pulse trains at the frequency of 66.7 and 80 GHz, the jitter saturates with increasing number of junctions. Kaplunenko suggested that SFQ pulses propagating through a JTL repulse each other when the time interval between adjacent pulses is smaller than that corresponding to the specific frequency, [8]. The value of specific frequency estimated for the parameters of junctions fabricated by NEC's Nb standard process is about 50 GHz, which agrees with the result of simulation.…”
Section: B Sfq Pulse Behaviors In Jtlsupporting
confidence: 81%
“…The obvious difference is the transient speed, which is related to the characteristic frequency. Therefore, we normalized the clock frequency by the characteristic frequency given in [14] …”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate the large influence of decision jitter limiting the maximum clock frequency of a counter flow shift register. All results scale with the characteristic voltage of the fabrication process and we could estimate the maximum clock frequency of the shift register to be in the order of the estimated maximum speed of digital signal processing in RSFQ circuits [5].…”
Section: Discussionmentioning
confidence: 99%
“…The normalization shows an independent transition width of (5) and the mean transition time is only slightly increasing for higher current densities. If the data arrives far before the clock pulse, we obtain the smallest delay as well as the smallest jitter for the readout pulse.…”
Section: Decision Jitter and Timing Of The Dffmentioning
confidence: 94%
See 1 more Smart Citation